Resource Dynamics In The Process Of Formal Voluntary Participation : A Case Study Of Friends Of Nature, China - Diao, Na (2010)
Voluntary organisations have become increasingly visible players in social transforming process of Chinese society. Every year, Chinese people from all walks of life actively take part in activities of these organisations. They become life force of these organizations. However, empirical research that examines the process in which volunteers take part in activities of these organisations – the process of formal voluntary participation - is less prevalent. In particular, understanding of insights and viewpoints of Chinese volunteers who work in the voluntary organisations is still limited. Therefore, knowledge of this topic is valuable for practitioners as well as for the social scientists. This thesis reports on the study undertaken to elucidate the underlying dynamics of the process of voluntary participation by employing a resource perspective. This research attempts (1) to understand volunteers’ insights of the underling dynamics which make the process of formal voluntary participation sustainable and dynamic; and (2) to capture the indigenous concepts in the context of voluntary participation of Chinese volunteers as they appeared in the case study of a Chinese voluntary organisation.